2021
DOI: 10.3390/ijerph18030876
|View full text |Cite
|
Sign up to set email alerts
|

Severe Suicidality in Athletes with Chronic Traumatic Encephalopathy: A Case Series and Overview on Putative Ethiopathogenetic Mechanisms

Abstract: Chronic traumatic encephalopathy (CTE) results from repetitive brain injuries and is a common neurotraumatic sequela in contact sports. CTE is often accompanied by neuropsychiatric symptoms, which could escalate to suicidal ideation (SI) and suicidal behaviour (SB). Nevertheless, fairly limited emphasis about the association between suicidality and CTE exists in medical literature. Here, we report two cases of retired professional athletes in high contact sports (boxing and ice hockey) who have developed simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 109 publications
0
9
0
Order By: Relevance
“…At the biomolecular level, we postulate that the etiopathogenic mechanism of SA in this population is associated with chronic, exacerbated neuroinflammatory process associated with both chronic headache/migraine, TBI, and SA. 9 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the biomolecular level, we postulate that the etiopathogenic mechanism of SA in this population is associated with chronic, exacerbated neuroinflammatory process associated with both chronic headache/migraine, TBI, and SA. 9 …”
Section: Discussionmentioning
confidence: 99%
“…Having a history of TBI increases risk for suicidal ideation, 5 suicide attempts (SA) 6,7 and death by suicide. [8][9][10] Specifically, an increased risk of suicide has been reported in veterans with TBI and retired athletes with chronic traumatic encephalopathy. 9,10 Headaches, arthritis, and back pain have lifetime rates of SA that range from 5% to 14% in the civilian population and commonly result in chronic pain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…114 In some individual case studies and series, suicide was observed in persons with CTE, including but not limited to athletes. [115][116][117][118][119][120] An analysis of 85 brain specimens from former athletes, military veterans, or civilians with histories of repetitive mild TBI found CTE in 80% of the cases with 26% experiencing suicidal ideation and 14% of deaths occurring due to suicide and 12% due to substance abuse. 121 Mez et al 122 reported that 87% of 202 deceased American Football Players were diagnosed with CTE, 96% of them featured psychiatric conditions during their lifetime, including depression (67%), anxiety (52%), impulsivity (89%), substance abuse (67%), and suicidality (56%).…”
Section: Chronic Traumatic Encephalopathymentioning
confidence: 99%
“…[ 3 ] The multiple factors of the mental health problems include general factors (e.g., stressful life events and inadequate social support) and athlete-specific factors (e.g., physical injury, poor performance, competition for selection, career transition). In addition, contact sports athletes may exhibit mental health symptoms and associated suicidal behavior due to biological causes such as chronic traumatic encephalopathy [ 4 ]. The usual definition of an elite athlete is an athlete who competes at a national or international level, including athletes in the domestic league [ 5 ].…”
Section: Introductionmentioning
confidence: 99%